PENGARUH MEDIA TERKONDISI SEL PUNCA MESENSIMAL TERHADAP EKSPRESI GEN TRANSCRIPTION FACTOR 7-LIKE 2 (TCF7L2) TIKUS MODEL DIABETES MELITUS TIPE 2 - Stefani Santi Widhiastuti; Bernadia Branitamahisi; Nor Sri Inayati; Ida Ayu Preharsini; Demas Bayu Handika; Ahmad Hamim Sadewa; Abdurahman Laqif; Sofia Mubarika Haryana (BERITA BIOLOGI, 2020)
Diabetes mellitus type 2 is the most common type of diabetes. This study was conducted to determine the effect of Mesenchymal Stem Cell-Conditioned Medium (MSC-CM) in Homeostatic Model Assessment of β-cell function (HOMA-β) value, normal Langerhans cells, and Transcription Factor 7-Like 2 (TCF7L2) gene expression in type 2 diabetic rats model. As many as 27 male Sprague Dawley rats were divided into 3 study research groups: normal control (9 normal rats), diabetic control (9 type 2 diabetic rats, induced by 60 mg/kg BW Streptozotocin and 120 mg/kg BW Nicotinamide i.p.), and treatment (9 type 2 diabetic rats treatment with 0.1 ml/200g BW MSC-CM i.p.). On day 30 after therapy, the expression of TCF7L2 gene was performed with real time-quantitative PCR (RT-qPCR). The HOMA-β value were calculated based on Fasting Insulins (FINs) levels and Fasting Blood Glucose (FBG) levels data from other research team members. Based on results, MSC-CM increases the HOMA-β value and amount of normal Langerhans cells of treatment group that indicates amelioration effect of MSC-CM, but there was no significant difference in TCF7L2 gene expression level between diabetic control and treatment group.